Synthesis and characterization of Cu(II), Co(II), Ni(II) and Zn(11) Schiff base complexes from 1-amino-5-benzoyl-4-phenyl-1H-pyrimidine-2-one with salicylaldehyde - Sönmez, M; Sekerci, M (Polish Chemical Society, 2002)
Cu(II), Co(II), Ni(II) and Zn(II) metal complexes of new heterocyclic Schiff base derived from 1-amino-5-benzoyl-4-phenyl-1H-pyrimidine-2-one with salicylaldehyde have been synthesized and characterized by elemental analyses, mass, electronic, IR and H-1 NMR spectra, and also by molar conductivity measurements, magnetic moment measurements and thermogravimetric analyses (TGA). It has been found that the Schiff bases behave as a neutral bidentate (NO) and tridentate (ONO) ligands forming chelates with 1:2 (metal:ligand) stoichiometry. Octahedral environment is suggested for metal complexes. The conductivity data for the Ni(II) complexes are consistent with those expected for an electrolyte.
Keywords: Schiff bases complexes; salicylaldehyde; 1-amino-5-benzoyl-4-phenyl-1-H-pyrimidine-2-one